Expectations gap between auditors and user of financial statements in the audit process: an auditors' perspective / Ahmad Adnan Toumeh, Sofri Yahya and Walid Zakaria Siam. - Toumeh, Ahmad Adnan; Yahya, Sofri; Siam, Walid Zakaria (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
The study aimed at identifying the factors that affect the expectation gap in the audit process from the auditor’s point of view in Jordan, and in addition to suggest some solutions that may narrow the expectations gap to a least possible extent. To achieve the study objectives, a questionnaire was designed and distributed to auditors who work in audit firms in Jordan. The number of valid questionnaires for analysis was 109 out of 158 that were distributed, which means 69% of the total number of questionnaires. Statistically speaking, results showed that the external auditors in Jordan have a conception for expectations gap. From their point of view, the lack of awareness (unreasonable expectations) amongst users of financial statements has the greatest impact on increasing the expectations gap. On the other hand, they believe that ‘’uncertainty” in the auditor’s independence has less impact on increasing the expectations gap in the audit process in Jordan. In light of the study results and to narrow the expectations gap in the audit process in Jordan, the researchers recommend the need to strengthen an auditor’s independency, by neutralizing the controls of the disputing parties and reducing the personal relations between the auditor and the client, enhancing the role of the Jordan Association of Certified Public Accountants (JACPA) and activating its role on supervising the auditing profession by urging auditors to comply with international auditing standards, code of professional conduct, and applying legalisations.